Concussion and strength performance in youth ice hockey players. Issue 5 (11th March 2013) - Reed, Nick; Taha, Tim; Keightley, Michelle L
Abstract : Objective: To explore the influence of concussion on strength performance within youth ice hockey players. Design: Athletes were assessed prospectively before and after a sport-related concussion and longitudinally across a 3-year period. Setting: University research laboratory. Participants: 178 unique male and female youth ice hockey players (ages 8–14 years). Nineteen of the 178 participants sustained a concussion while enrolled in the study, where three participants sustained repeated concussions for a total of 23 concussive events. Intervention: Participants completed a pre-season/baseline assessment of strength performance annually for up to 3 years. If a concussion was sustained, follow-up assessment on the same measures was. Outcome Measures: Lower body and upper body strength performance (leg maximal voluntary contraction, squat jump height, counter movement jump height and hand grip). Results: Using a linear mixed-effects model, when accounting for severity of post-concussive symptoms, significant average effects were found for jump height (squat jump: Estimate=−0.05; SE=0.02; t=−2.51; P=0.0186; countermovement jump: Estimate=−0.03; SE=0.02; t=−2.20; P=0.0371) during the symptomatic stage post-concussion and for leg maximal voluntary contraction (Estimate=−1.05; SE=0.47; t=−2.27; P=0.0421) during the asymptomatic stage post-concussion, indicating decreased strength performance following concussion. Conclusions: This study acts as an initial step towards better understanding concussion-related strength performance deficits that may limit the on and off ice performance of the youth ice hockey player population. Acknowledgements: Ontario Neurotrauma Foundation (ONF). Competing interests: None.